2022
DOI: 10.1007/s00426-021-01636-w
|View full text |Cite
|
Sign up to set email alerts
|

Motor restrictions impair divergent thinking during walking and during sitting

Abstract: Creativity, specifically divergent thinking, has been shown to benefit from unrestrained walking. Despite these findings, it is not clear if it is the lack of restriction that leads to the improvement. Our goal was to explore the effects of motor restrictions on divergent thinking for different movement states. In addition, we assessed whether spontaneous eye blinks, which are linked to motor execution, also predict performance. In experiment 1, we compared the performance in Guilford’s alternate uses task (AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…We computed a blink detection algorithm based on the pupil radius data similar to the one described in previous studies (Brych & Händel, 2020; Brych, Murali, & Händel, 2021a, 2021b; Murali & Händel, 2021, 2022). First, the z‐score of the radius data of each eye was calculated (per trial, for each subject) and then a potential blink was considered if either (1) both left and right eye radii values were missing or (2) if either the left or right eye radii data were missing and the other eye had a z‐score below a threshold of −1 (Exception: Experiment 1: threshold set to −2 for four subjects; Experiment 2: threshold set to 0.5 for one trial for one subject and two trials for another subject).…”
Section: Discussionmentioning
confidence: 99%
“…We computed a blink detection algorithm based on the pupil radius data similar to the one described in previous studies (Brych & Händel, 2020; Brych, Murali, & Händel, 2021a, 2021b; Murali & Händel, 2021, 2022). First, the z‐score of the radius data of each eye was calculated (per trial, for each subject) and then a potential blink was considered if either (1) both left and right eye radii values were missing or (2) if either the left or right eye radii data were missing and the other eye had a z‐score below a threshold of −1 (Exception: Experiment 1: threshold set to −2 for four subjects; Experiment 2: threshold set to 0.5 for one trial for one subject and two trials for another subject).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that holistic physical practices influence planning and creativity outcomes 108 . Specifically, researchers have proposed that the mechanism linking PA to creativity is not a link between exercise and cognition but that the broadening of attention during free movement compared to restricted movements 111 , 112 . Murali and Händel 111 conducted three experiments in adults involving sitting and walking to identify the mechanism between movement and creativity through restricting movement in both activities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, researchers have proposed that the mechanism linking PA to creativity is not a link between exercise and cognition but that the broadening of attention during free movement compared to restricted movements 111 , 112 . Murali and Händel 111 conducted three experiments in adults involving sitting and walking to identify the mechanism between movement and creativity through restricting movement in both activities. They found that free movement led to better performance in creativity tasks due to broadening of focus of attention (see also 112 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three studies investigated the effect of exercise on cognitive flexibility. They assessed walking of less than 15 min at light intensity either on a treadmill ( Oppezzo and Schwartz, 2014 ; Tomporowski and Audiffren, 2014 ) or on the floor ( Murali and Händel, 2022 ) and consistently found beneficial effects. In sum, short walking interventions increase cognitive flexibility.…”
Section: Methodsmentioning
confidence: 99%